Analysis of the economic viability of the peanut crop in the region of Jaboticabal, São Paulo - De Moraes Farinelli, Juliana Borba [UNESP]; Horita, Kandy [UNESP]; Santos, David Ferreira Lopes [UNESP] (UNESP - Universidade Estadual Paulista, 2018)
This study analyzes the economic viability of peanut cultivation by small rural enterprises in the Jaboticabal region. The use of peanut as a rotation crop in sugarcane renewal areas demands a specific and incremental economic and financial analysis from rural producers, considering that this product requires fixed assets and procedures distinct from the sugarcane crop and, therefore, it is necessary to identify under what conditions peanut cultivation can be profitable to the producer. A quantitative and qualitative approach was used through discounted cash flow combined with cost-volume-profit analysis. It was verified that the economic viability of peanut occurs in areas greater than 88 hectares. Considering the average profile of the region, of 100 ha of planting per year, the rural producer can achieve a Net Present Value (NPV) of R$ 6,480/ha, and an Internal Rate of Return (IRR) of 13.94%, which ensure the economic viability of this crop in a rotation system with sugarcane.
Keywords: Arachishypogaea L; Cost-volume-profit; Discounted cash flow; Economic viability; Yield